Environmental Education in Thai High Schools: The Insights into Learning Objectives and Pedagogical Approaches - Channakorn, Sarayoot; Boonsoong, Boonsatien; Ketsing, Jeerawan (วารสารพัฒนาการเรียนการสอน มหาวิทยาลัยรังสิต, 2026)
Environmental Education (EE) has been recognized by the United Nations Sustainable Development Goals (SDGs) as a vital component in fostering environmentally literate citizens and promoting global sustainability. However, despite its acknowledged importance, there is limited understanding of how high school teachers integrate EE into authentic learning environments. Existing literature on environmentally EE has predominantly concentrated on interventions and their effects on environmental knowledge, proenvironmental behaviors, and related outcomes. This study employed simple random sampling to select 42 teachers from 22 secondary schools regarding their learning objectives and pedagogical approaches in EE. The respondents were selected from three groups of teachers: 1) biological or environmental science teachers, 2) social studies or civic education teachers, and 3) advisors for assemblies or extracurricular activities related to EE or sustainable development. The data were systematically analyzed by calculating the frequency and percentage distributions of the respondents’ selections, as well as identifying the key learning objectives and pedagogical approaches utilized by the teachers. The findings indicated that the primary goals of EE were the application of knowledge, the cultivation of environmental values, and the acquisition of environmental knowledge. The most commonly employed pedagogical approaches included traditional lectures, inquiry-based learning, and problem-based learning. Conversely, less frequently adopted approaches encompassed place-based learning, emancipatory approach, and action project learning. The study further revealed that classroom-based EE tended to prioritize knowledge acquisition and its practical application, rather than fostering students’ ability to initiate environmental change through collaboration with relevant stakeholders. These findings highlight the necessity for expanding the repertoire of pedagogical approaches in EE and advocate for a shift towards more proactive, capacity-building approaches that encourage collaborative networks. Such an approach would empower students to actively engage in addressing environmental challenges.